Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations and it is of essential importance that he should be enabled to obtain the specialised orthopaedic treatment on which not only his own but his family's future may depend. A bigger register of cases causes also more work for the Training and Welfare Department, which has (as will be seen in the section dealing with this department) doubled the numbers on its Home Industry Register alone. A grateful tribute is due to the unflagging energy and invaluable services of the Hon. Secretary, Mrs. John Radcliffe. The printing of the Quarterly Letter for circulation to Local Representatives is now established, and the assistance of the Press in finding space to publish a summary of it is a further gratefully noted instance of their readiness to co-operate with D.A.C.A. on all possible occasions. The Voluntary Fund Capital Account (p. 35) shows a credit balance of £312 14s. 7d., but against this must be set the loan of £1,200 from the Building Extension Account for the purchase of land adjoining the Hospital. By the generosity of the vendor this land was acquired on particularly favourable terms, and its possession permanently protects the amenities of the Hospital site. Thanks to the assistance of many kind supporters, the Income Account is in credit to the extent of £97 16s. 16d. Several donations have been accompanied by appreciative tributes to the Association's work, and a substantial contribution resulting from University College Rag Day has again been a welcome item. It is a matter of profound gratitude that the amount received in subscriptions (which includes some not paid in 1931) is slightly more than hitherto, despite the hard times. Nevertheless, the growth of D.A.C.A.'s activities necessarily involves increased expenditure, and further subscriptions, however small, are ardently desired. In this connection it cannot be too clearly emphasized that, admirable and deserving as is the work done by the various national organisations for the welfare of cripples, it is not on them but on this Association that the cripples in its area must depend for treatment and assistance, while it is only within the confines of its own area that D.A.C.A. can appeal for financial support. Although the Hospital Extension Fund shows a credit balance of £1,416 6s. 0d. (in addition to £1,200 loaned to Capital Account) and the Angela Convalescent Home Account a credit of £1,503 18s. 3d., the liabilities incurred in connection with these two developments amount to approximately £14,000, of which not more than £7,000 has been received or promised. The Committee has decided to make an appeal for the balance required, and the task of raising this amount must be the main enterprise of 1933. It is the first organised appeal which D.A.C.A. has made since the Hospital was built in 1927. 4 292/841.51/2/2